Metodologia de priorização de atividades para a implementação do plano de manejo de unidade de conservação - PARISE, Giselle Gouvêa (Universidade Federal do Pará, 2018)
Brazil is one of the world's richest country in biodiversity and in order to effectively protect this biodiversity and other natural resources, Conservation Units (CU) are created with federal, state or municipal jurisdiction. However, creating not only ensures its protection, and for this, it was legally established that they would have a period of 05 years to develop their management plans, the main instrument of planning Unit, which establishes the zoning and standards of the area. The fact is that management plans drawn up are hardly implemented due to various reasons, including: lack of human resources, finance, and preparation not consistent as a working tool applied to the manager because their massive actions to be implemented. In order to optimize the directions of the efforts in UC, this dissertation aims to develop a methodology to prioritize activities to implement the Management Plan for the Conservation Unit, which is composed of identifying the structural variables of the Management Plan, use of AHP method, and refinement of prioritization with universal criteria. In order to check and to improve the methodology, it was performed a case study in the Management Plan of Serra dos Martírios/Andorinhas’s. This methodology proved quite satisfactory, serving with an effective tool to support decision making by managers.